Pengaruh Keunggulan Kompetitif Dan Kualitas Pelayanan Terhadap Kepuasan Dan Loyalitas Pengunjung Objek Wisata Air "Owabong" Purbalingga - Ahmadia, Eru; Drs. M. Farid Wajdi, MM.,Ph.D (2017)
ABSTRACT This study aims to determine and analyze the effects of competitive advantage and service quality to customer satisfaction, and the subsequent impact on the loyalty of Owabong Water Park Purbalingga visitors. This research is a descriptive causal research, using survey method. The population of the research is Owabong Water Park visitors. This research uses a sample of 100 visitors. The sampling is done through convenience sampling technique. Data in this study are collected from questionnaires distributed to the samples, and other secondary data available. The data analysis is done using path analysis. Based on the analysis, the study concludes that: the competitive advantage and service quality have positive and significant effect on customer satisfaction either partially and simultaneously; customer satisfaction has a positive and significant effect on customer loyalty; competitive advantage and service quality do not have a direct effect on customer loyalty; and there are indirect effects of competitive advantage and service quality to customer loyalty through customer satisfaction. Keywords: Customer loyalty, customer satisfaction, competitive advantage, service quality.